2014
DOI: 10.1155/2014/823853
|View full text |Cite
|
Sign up to set email alerts
|

The Overlap of Dietary Supplement and Pharmaceutical Use in the MIDUS National Study

Abstract: Introduction. In the United States, dietary supplement (DS) use is common, often takes place outside of the purview of health care providers, and may involve DS in combination with pharmaceuticals. This situation has led to concerns about interactions between DS and pharmaceuticals, as well as the risks from polypharmacy and polysupplement use. Methods. We used data from the Midlife in the US study (MIDUS 2 Survey) to examine DS and prescription pharmaceutical use in 3876 study participants in order to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…14 Other studies have corroborated the correlation between DS use and the use of OTC and prescription medications. 10,21 With respect to diagnoses, significantly increased DS use was found among participants with eye disease (including glaucoma), cancer, elevated lipids, and arthritis, though these trends were found to be non-significant with the adjusted statistical analysis. Although study participants with physician-diagnosed elevated lipid levels showed borderline increased DS use (unadjusted), there was no difference in mean total cholesterol or triglycerides lab values between groups, though there was higher HDL (median 55 to 52) and lower glucose (median 96 to 97) amongst DS users.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…14 Other studies have corroborated the correlation between DS use and the use of OTC and prescription medications. 10,21 With respect to diagnoses, significantly increased DS use was found among participants with eye disease (including glaucoma), cancer, elevated lipids, and arthritis, though these trends were found to be non-significant with the adjusted statistical analysis. Although study participants with physician-diagnosed elevated lipid levels showed borderline increased DS use (unadjusted), there was no difference in mean total cholesterol or triglycerides lab values between groups, though there was higher HDL (median 55 to 52) and lower glucose (median 96 to 97) amongst DS users.…”
Section: Discussionmentioning
confidence: 81%
“…A complete description of the MIDUS project and methodology is available in prior publications. 10,18 To augment the self-reported data collected in the MIDUS survey project, participants completed a medical history, selfadministered questionnaire, and self-reported sleep assessments (see below).…”
Section: Midus 2 Project 4 Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIDUS has collected more than 20 years of data on complementary health approach use, but thus far only cross-sectional analyses have been conducted on data of complementary health approach use from wave 1 (1995-1996) to wave 2 (2004-2005) of data collection. [1][2][22][23][24]…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, dietary supplements are a pervasive form of preventative, adjunctive, and alternative healthcare [1][2][3][4][5][6][7][8][9][10]. More than half of US adults use di-…”
Section: Introductionmentioning
confidence: 99%